A Novel Method for Uniform Nano Liposomes Using Focused Ultrasonic Technology - Ji-Soo Yun; Seonae Hwangbo; Young-Gyu Jeong (Chemical and Materials Sciences - Developments and Innovations Vol. 1, 2024)
Liposomes, spherical structures formed by phospholipids in aqueous solutions, serve as valuable carriers for both hydrophilic and hydrophobic substances, finding wide application in cosmetics and pharmaceuticals. The ideal liposomal properties include small size, uniform distribution, and long-term stability. Traditional methods such as homo mixers, microfluidizers, and sonicators have limitations in achieving these criteria. To address this, we propose a focused ultrasound technique for producing nano-sized liposomes with enhanced size control. In our study, liposome solutions were prepared using both focused ultrasound and conventional methods. The resulting solutions were then analyzed for size distribution, stability, and morphology. Our findings reveal that liposomes generated via focused ultrasound exhibited a uniform particle size distribution, with an average size of 113.6 nm and a polydispersity index of 0.124. Moreover, these liposomes demonstrated excellent stability over time, as evidenced by dynamic light scattering measurements up to 4 days and Turbiscan assessments over a week.